Effect of zinc stearate on the rheology of ionic elastomer based on carboxylated nitrile rubber - Mandal, U. K.; Tripathy, D. K.; De, S. K. (Polymer engineering and science, 1996)
Monsanto rheometry, melt viscometry, differential scanning calorimetry, and dynamic mechanical spectroscopy have been used to study the effects of zinc stearate on the rheological behavior of ionomer based on carboxylated nitrile rubber (XNBR) ‐ zinc oxide (ZnO) system. At temperatures below its melting point, zinc stearate functions as a reinforcing agent for ionomer formation. Above its melting point, it acts as a plasticizer for the ionic domains, thereby facilitating easy processing of the ionomer.